2011
DOI: 10.1177/0269216311407693
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in length of stay in hospice care by tumor stage in a large elderly cohort with non-small cell lung cancer

Abstract: This study examined whether there are racial disparities for length of stay in hospice for patients with non-small cell lung cancer (NSCLC).We studied 53,626 deceased patients aged ≥66 years diagnosed with American Joint Committee on Cancer stages I-IV NSCLC identified from the Surveillance, Epidemiology, and End Results-Medicare linked data who used hospice services in the last six months before death, and died between 1 January 1991 and 31 December 2005. Median time (days) and percent length of stay in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…However, it should be noted that conflicting results on the relationship between histological subtypes of lung cancer and ethnicity have been reported. [14][15][16][17][18][19] In contrast to our findings, a recent study in the USA on 1 812 African American patients with lung cancer, reported that 41.8% had adenocarcinoma and 20.6% SCC. 20 Apart from smoking status and total number of pack years, other factors that could possibly contribute to the observed differences in patients with lung cancer of African and Caucasian ethnicity have been investigated and reported in the literature.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that conflicting results on the relationship between histological subtypes of lung cancer and ethnicity have been reported. [14][15][16][17][18][19] In contrast to our findings, a recent study in the USA on 1 812 African American patients with lung cancer, reported that 41.8% had adenocarcinoma and 20.6% SCC. 20 Apart from smoking status and total number of pack years, other factors that could possibly contribute to the observed differences in patients with lung cancer of African and Caucasian ethnicity have been investigated and reported in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…Hardy et al 14 found that 69.1% of black patients were in the poorest quartile, as opposed to 19% of white patients, in a comparative study on patients with lung cancer in the USA. Conversely, 27.6% of white patients were in the highest quartile, compared to only 5.1% of black patients.…”
Section: 29mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of California dual eligibles found that blacks were 26% and Asians 34% less likely than whites to use hospice. Others have found similar results among patients with CHF and lung cancer …”
Section: Discussionsupporting
confidence: 71%
“…The patient’s physician will then select a new drug or combination, and the cycle will repeat itself, although with each subsequent cycle the probability of achieving a response becomes less and the duration of remission becomes shorter: 2–10 months for the second-line therapy, 0–5 months for the third-line and so forth. After receiving a therapy that is unsuccessful, the patient’s cancer grows, the performance status of the patient declines and they are deemed no longer fit enough to receive drug therapy, with death usually following within less than 1 month [2]. It is the goal of cancer physicians and scientists to change this natural history of cancer.…”
Section: Rationale For Fluid Biopsymentioning
confidence: 99%